PENERAPAN METODE (STRUKTURAL ANALITIK SINTETIK) SAS UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS II MI NW AIK BUKAQ TAHUN PELAJARAN 2022/2023 - Saharudin; Muh. Thala'at; Rostiana (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2022)
Application of the SAS Method to Improve Reading Ability in Indonesian Language Learning in Class II MI NW Aik Bukaq Academic Year 2022/2023. Madrasah Ibtidaiyah Teacher Education Study Program, Tarbiyah Faculty, Hamzanwadi Islamic Institute, NW, East Lombok, 2023. Reading is one of the aspects studied in key Indonesian language lessons or a source of knowledge possessed by a person is obtained through reading. This research aims to find out whether the SAS (Synthetic Structural Analytical) method can improve the reading ability of Class 2 MI NW AIK BUKAQ, and to determine the improvement in reading through the application of the SAS (Synthetic Structural Analytical) method for Class 2 MI NW AIK BUKAQ students. The method used in this research is the PTK method. The method used by PTK refers to the planning, implementation, observation and reflection model. The data from this research were obtained using observation sheets, and initial reading assessment rubrics, then this data was analyzed using a percentage formula. The results of the research obtained were that the increase in students' reading ability was obtained in cycle 1 which was 83% and in cycle II the increase in students' reading ability was 94%. Based on the research results, it can be concluded that applying the SAS method can improve students' reading abilities.